REFINEMENT OF TEST METHODS FOR ADHESIVE JOINT STRENGTH BASED ON NUMERICAL SIMULATION - Sevodina, N.V.; Fedorov, A.Yu. (Perm Federal Research Centre Journal, 2014)
Different variants of adhesive joint strength tests are considered and numerical analysis of the stress-strain state in tested specimens is carried out. The obtained results are compared with the methods generally used to estimate the stress-strain state. The optimal variants of geometry in the vicinity of singular points of specimens are determined based on the solution of the stated optimization problem. The obtained data lend support to a qualitative conclusion that the optimal surfaces exhibit common properties associated with the structure of solution at the vertex of the corresponding composite wedge, which defines the character of singular solutions at the points of contact of dissimilar materials under different conditions on the contact surface - perfect adhesion, dry friction, perfect slip.